Measurement and analysis of the efficiency of human capital in a small enterprises in Poland - Anna Bagieńska (e-Finanse: Financial Internet Quarterly, 2015)
Human capital plays an important role in the development of every company. Big enterprises have a Human Resources Department which conducts analyses and measurements of human capital. In Poland over 90% of the total number of companies is made up of small and middle- size enterprises. The aim of the research is to determine reasons why small Polish companies take an interest in the measurement and analysis of human capital as well as to discover the causes of their limited use of human capital measurement. The results confirmed that limited measurement and analysis of human capital efficiency in small companies results from the lack of additional information; apart from this it results from the binding legal regulations as well as the lack of employees who possess the knowledge necessary for conducting such analyses. Despite barriers and difficulties in human capital measurement, small companies appreciate employees and their qualification, not treating them only as a necessary cost of their doing business.
Keywords: L21; M21; M12; 330; Human Capital; Efficiency; Return on Investment; Productivity; Small Enterprise